The absorption of European Funds for the Romanian environmental sector - ŢURLEA, Eugeniu; ŞERBAN, Mihaela; ALBERT, Valeria Maria (Annals of Spiru Haret University. Economic Series, 2011)
This paper shows the impact of grants on the importance of access to funds to protect the environment and the structural funds absorption environmental sector in Romania. Study research methodology is based on references to achieve the objectives pursued in this article.